2021
DOI: 10.3390/met11101622
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Plastic Deformation in Mathematically-Designed Architected Cellular Materials

Abstract: The ability to control the exhibited plastic deformation behavior of cellular materials under certain loading conditions can be harnessed to design more reliable and structurally efficient damage-tolerant materials for crashworthiness and protective equipment applications. In this work, a mathematically-based design approach is proposed to program the deformation behavior of cellular materials with minimal surface-based topologies and ductile constituent material by employing the concept of functional grading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…This feature, however, poses a drawback in the case of brittle constituents: when one unit cell fails, the other unit cells will successively fail under critical compression loading, causing a sudden and catastrophic failure in the structure . This detrimental failure mode prevents early detection of failure, prompting the development of asymmetric cellular materials, which are materials consisting of heterogeneous microstructures. …”
Section: Asymmetric Cellular Structuresmentioning
confidence: 99%
“…This feature, however, poses a drawback in the case of brittle constituents: when one unit cell fails, the other unit cells will successively fail under critical compression loading, causing a sudden and catastrophic failure in the structure . This detrimental failure mode prevents early detection of failure, prompting the development of asymmetric cellular materials, which are materials consisting of heterogeneous microstructures. …”
Section: Asymmetric Cellular Structuresmentioning
confidence: 99%
“…To conclude, although the dataset is very restricted and confined, functional gradation strategy seems very promising in terms of enhancing the compressive stiffness and strength of TPMS structures. Unifrom D [114] Uniform G [114] Longitudinal hybrid [114] Radial hybrid [120] Unifrom G [117] Stochastic G [117] Stochastic sheet-based [118] RDG1T [98] RDG1T [98] RDG2 [98] RDG3 [98] CSG1 [98] CSG2 [98] CSG2T [98] CSG3 [98] Uniform Sheet G [100] Graded G [100] Graded Rhombic [101] Unifrom P [101] Graded Arrows [101] Unifrom P [101] ρ Unifrom G [117] Stochastic G [117] RDG2 [98] RDG3 [98] CSG1 [98] CSG2 [98] CSG2T [98] CSG3 [98] Uniform Sheet G [100] Graded G [100] Graded Rhombic [101] Unifrom P [101] Graded Arrows [101] Unifrom P […”
Section: Hybridization Of Tpms Structuresmentioning
confidence: 99%
“…Almesmari et al [128] reported that for mesoscale structures, the geometrical deviation between the as-built and as-designed lattices increased as their aspect ratio (i.e., ratio of cell wall thickness to unit cell size) approached the minimum resolution of an FDM printer. Jiang and Ning [129] utilized the printing-debinding-sintering Unifrom D [114] Uniform G [114] Longitudinal hybrid [114] Radial hybrid [120] Unifrom G [117] Stochastic G [117] Stochastic sheet-based [118] RDG1T [98] RDG2 [98] RDG3 [98] CSG1 [98] CSG2 [98] CSG2T [98] CSG3 [98] Uniform Sheet G [100] Graded G [100] Graded Rhombic [101] Unifrom P [101] Graded Arrows (PDS) process to fabricate BCC, FCC, and BCC-FCC plate lattices made of 17-4 stainless steel in a multistep procedure consisting of FDM printing of metal-polymer composites, debinding the printed pats (i.e., green parts) to remove polymeric wax and then sintering the components in a furnace to improve the layers binding strength. Utilization of the PDS process seems very promising to enhance the printing accuracy of the conventional FDM technology.…”
Section: Plate Lattice Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 3, the feature being graded is the width of the rectangular unit cell, which increases from left to right. In addition to modulating cell size, it is also possible to spatially prescribe variations in wall thickness, even with discrete step changes in value, as shown in one example from the published literature in Figure 4a [19]. With advances in simulation capabilities, particularly with topology optimization, it is possible to prescribe these gradients in response to a field derived from simulation [20,21].…”
Section: Types Of Aperiodic Cellular Materialsmentioning
confidence: 99%